Content knowledge of undergraduate students in solving the algebra’s problem - Bani, Blandina Seko; Fuad, Yusuf; Ekawati, Rooselyna (Edelweiss Applied Science and Technology, 2025)
Content knowledge (CK) is essential in mathematics education, particularly for understanding algebraic concepts. This study explores the algebraic content knowledge of undergraduate mathematics education students. Using a descriptive qualitative approach, the research involved third-year students from a private university in East Nusa Tenggara, Indonesia. Two validated instruments, the Diagnostic Test (TD) and the Content Knowledge Test (TCK), were employed to assess students' understanding. The instruments showed strong validity scores, with 4.6 for the TD and 4.0 for the TCK (on a 5-point scale), and reliability scores of 0.9993 for the TD and 0.9983 for the TCK. Data were analyzed using two frameworks: the Direct Translation Approach (DTA) and the Meaning-Based Approach (MBA). Findings revealed varied levels of CK: some students demonstrated procedural fluency and the ability to relate symbolic representations to contextual meaning (MBA), while others exhibited difficulties in applying concepts flexibly, leading to illogical reasoning (DTA). These outcomes highlight the need to strengthen conceptual understanding and reflective thinking among pre-service teachers. The study recommends instructional strategies that integrate symbols, context, and meaning to enhance students' ability to solve algebraic problems effectively. Such approaches are crucial for preparing future mathematics teachers capable of connecting mathematical reasoning to real-world contexts.